x + y = 3 x + 3 y = x y = 3 3 8 3 1 7 ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Nice substitution Guillermo
Log in to reply
Wrong place ....see where you have written your comment...
Log in to reply
Thank you Shashank, your solution, Rishabh, is cool too... Please,don't argue each other... The important is everything is allright and everybody is happy...
Log in to reply
@Guillermo Templado – No- nothing to argue ... I was just saying to write it at appropriate place so that the comment doesn't appear awkward.... :-)
Log in to reply
@Rishabh Jain – Yup,I for seeing this comment, Shashank had to write it under my solution, but I have seen it, so everything is allright at the end... :P
Let's call x = a 3 , y = b 3 ⇒ a 3 + b 3 = 3 3 8 3 , a + b = 1 7 and then a 3 + b 3 = 3 3 8 3 = ( a + b ) ⋅ ( a 2 − a b + b 2 ) = 1 7 ⋅ ( a 2 − a b + b 2 ) ⇒ a 2 − a b + b 2 = 1 9 9 ( 1 ) , 1 7 2 = 2 8 9 = a 2 + 2 a b + b 2 ( 2 ) Substrating ( 1 ) to ( 2 ) we get 2 8 9 − 1 9 9 = 9 0 = 3 a b ⇒ a b = 3 0 ⇒ x y = a 3 ⋅ b 3 = ( a b ) 3 = 2 7 0 0 0
Rishabh, nice solution. But I simply made assumptions that to get 17... we need two no.s such that their no. Of digits is at least 3 in each case because when they add up , they give 3383. So , the possible combinations are 9,8 10,7 11,6 12,5 ..... and the last one 16,1. In all of these you find that 15 cube gives 3375 which is almost 3383. So, The Magical Combination is 15,2. Thus 15 cube i.e, 3375 and 2 cube i.e, 8 gives a product
3375×8=27000
x + y = ( 3 x + 3 y ) ( 3 x 2 − 3 x y + 3 y 2 ) = 3 3 8 3
Substituting ( 3 x + 3 y ) = 1 7
1 7 ( 3 x 2 − 3 x y + 3 y 2 ) = 3 3 8 3
And 3 x 2 − 3 x y + 3 y 2 = 1 9 9
Then, ( 3 x + 3 y ) 2 − ( 3 x 2 − 3 x y + 3 y 2 ) = 3 3 x y = 2 8 9 − 1 9 9 = 9 0
Finally, 3 x y = 3 0 and x y = 3 0 3 = 2 7 0 0 0
Problem Loading...
Note Loading...
Set Loading...
⟹ ⟹ ⟹ ⟹ ⟹ 3 x + 3 y = 1 7 x + y + 3 3 x y ( 3 x + 3 y ) = 1 7 3 3 x y = 3 ( 3 x + 3 y ) 1 7 3 − ( x + y ) x y = ( 3 ( 3 x + 3 y ) 1 7 3 − ( x + y ) ) 3 x y = ( 3 ( 1 7 ) 1 7 3 − ( 3 3 8 3 ) ) 3 x y = ( 3 0 ) 3 = 2 7 0 0 0
Formula used in second line: ( x + y ) 3 = x 3 + y 3 + 3 x y ( x + y )